Gender attitudes with regard to intra-family distribution of roles among Korean and Belarusian students - Truhan, Elena A.; Salivonchik, Alexandra A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article discusses the results of the first comparative analysis of gender indicators of Belarusian and Korean students regarding the distribution of roles within the family. It was revealed both the presence of egalitarian attitudes among Belarusian and Korean students (males and females) regarding the majority of family roles, and the stability of their traditional views on the realization of certain roles in the family by a man and a woman. There is a tendency to overcome the stereotypes of family roles distribution between the sexes among Korean respondents. Belarusian respondents generally demonstrated more coherence regarding gender role differentiation in the family.
Keywords: gender attitudes; gender role; gender stereotype; family role; egalitarianism; Belarusian students; Korean students